2017
DOI: 10.1038/s41598-017-04385-2
|View full text |Cite
|
Sign up to set email alerts
|

From shifting cultivation to teak plantation: effect on overland flow and sediment yield in a montane tropical catchment

Abstract: Soil erosion supplies large quantities of sediments to rivers of Southeastern Asia. It reduces soil fertility of agro-ecosystems located on hillslopes, and it degrades, downstream, water resource quality and leads to the siltation of reservoirs. An increase in the surface area covered with commercial perennial monocultures such as teak plantations is currently observed at the expanse of traditional slash-and-burn cultivation systems in steep montane environments of these regions. The impacts of land-use change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 44 publications
2
52
0
1
Order By: Relevance
“…Consequently, the temporal variation in suspended solids was consistent with the variation in surface runoff because both surface runoff and peak runoff rate determine the temporal variation in soil erosion in SWAT. Similar trends in both simulated surface runoff and simulated suspended solids were also reported in Ribolzi et al (2017).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Consequently, the temporal variation in suspended solids was consistent with the variation in surface runoff because both surface runoff and peak runoff rate determine the temporal variation in soil erosion in SWAT. Similar trends in both simulated surface runoff and simulated suspended solids were also reported in Ribolzi et al (2017).…”
Section: Resultssupporting
confidence: 80%
“…Therefore, we suggest further development of the hydrology submodule of SWAT to simulate the effect of the kinetic energy of raindrops falling from the canopy on soil erosion. Second, SWAT separates soil and land use management parameters, although previous studies revealed that different land use can change soil properties, such as saturated hydraulic conductivity (SOL_K) or bulk density (SOL_BD) (Patin et al, 2012; Ribolzi et al, 2017; Ziegler et al, 2004). In this study, we found that SOL_BD was highly ranked in the sensitivity analysis, but because of the model concept, it remained constant while land use changed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that in flat areas, RT monocultures decrease insect, bird and plant species richness and soil quality compared to forests (Beukema et al ., ), but are similar to or have slightly higher biodiversity and soil conditions than other tree plantations (Gnanavelrajah & Shrestha, ; Guillaume et al ., ). Various studies found that in mountainous areas tree plantations increased overland flow and sediment loss (Ribolzi et al ., ) and overall exacerbated soil degradation (Janeau et al ., ; Podwojewski et al ., ; Valentin et al ., ; Paiboonvorachat & Oyana, ). The processes and social implications of such trajectories have been discussed elsewhere (Fox & Castella, ; Ahrends et al ., ).…”
Section: Introductionmentioning
confidence: 97%